EVEREST II high risk study based UK cost-effectiveness analysis of MitraClip® in patients with severe mitral regurgitation ineligible for conventional repair/replacement surgery. (November 2013) - Mealing, Stuart; Feldman, Ted; Eaton, James; Singh, Moushmi; Scott, David A.
Abstract Objectives: To evaluate the cost-effectiveness of MitraClip, an interventional procedure for patients with chronic severe mitral regurgitation. Methods: A decision analytic model with a lifetime horizon was developed to assess the cost-effectiveness of MitraClip vs conventional medical management in patients with severe mitral regurgitation, ineligible for surgery. The analysis was performed from a UK NHS perspective and the estimates for mortality, adverse events, and cross-sectional NYHA class were obtained from the EVEREST II High Risk Study (HRS). Utility decrements were obtained from a heath technology assessment on Cardiac Resynchronization Therapy, while unit costs were obtained from national databases. The concept model was clinically validated. Costs (2011 £UK) and benefits were discounted at an annual rate of 3.5%. Results: Compared to medical management, over 2- and 10-year periods MitraClip had incremental Quality Adjusted Life Year (QALY) gains of 0.48 and 2.04, respectively. The Incremental Cost-Effectiveness Ratios for MitraClip at 2 and 10 years are £52, 947 and £14, 800 per QALY gained. Overall, the model was most sensitive to the choice of time horizon, the discount rate applied to benefits, the starting age of cohort, the utility decrement associated with NYHA II, and cost of the MitraClip procedure. The model was insensitive to changes in all other parameters. MitraClip was also found to be cost-effective, regardless of the modelling approach, and insensitive to the key assumptions of the procedure cost. Study limitations: The primary limitation of the analysis is the reliance on aggregate data from a modestly sized non-randomized study with a short-term follow-up period. Aligned to this was the need to extrapolate survival well beyond the study period in order to generate meaningful results. The impact of both of these limitations was explored via extensive sensitivity analyses. Conclusion: Compared to medical management, MitraClip is a cost-effective interventional procedure at conventional threshold values.